2002
DOI: 10.1159/000056054
|View full text |Cite
|
Sign up to set email alerts
|

Lumboperitoneal Shunting as a Treatment for Slit Ventricle Syndrome

Abstract: Objective: Slit ventricle syndrome (SVS) has been described in hydrocephalus patients who continue to have shunt malfunction-like symptoms in the presence of a functioning shunt system and small ventricles on imaging studies. These symptoms usually present years after shunt placement or revision and can consist of headache, nausea and vomiting, lethargy and decreased cognitive skills. Treatments offered range from observation, medical therapy (migraine treatment) and shunt revision to subtemporal decompression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 15 publications
0
37
0
1
Order By: Relevance
“…More recently Le et al [30]have reported the use of lumboperitoneal shunting in addition to a functioning ventricular shunt. This provided good relief in all of their 7 patients with non-compliant ventricle syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…More recently Le et al [30]have reported the use of lumboperitoneal shunting in addition to a functioning ventricular shunt. This provided good relief in all of their 7 patients with non-compliant ventricle syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…For most such cases, we advocate the use of LP shunts, which can drain both pathways. 15,34 In this case, however, the decision was complicated by the presence of the Chiari malformation Type II and NVH. We elected to explore the previous surgical site.…”
Section: Illustrative Cases 1 Andmentioning
confidence: 87%
“…Subsequently, the shunt failure resolved. Le and colleagues 15 reported that lumbar shunts selectively drained the CSAS after they observed that the lateral ventricles enlarged when an LP shunt was inserted for the treatment of SVS.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…It is also performed for the treatment of CSF fistula, idiopathic intracranial hypertension (Burgett et al, 1997) and slit-ventricle syndrome (Le et al, 2002). Complications such as infection and malfunction were reportedly lower in LP shunt than VP shunt (Aoki, 1990).…”
Section: Lumboperitoneal Shunt (Lp Shunt)mentioning
confidence: 99%